Peningkatan Keterampilan Menulis Cerpen Menggunakan Model Problem Based Learning Dengan Media Gambar Seri Pada Peserta Didik Kelas IX D SMP Negeri 2 Panggul Trenggalek - Kusmini, Kusmini (Universitas Nusantara PGRI Kediri, 2022)
In learning the material to examine the structure and linguistic aspects of short stories, many students of class IX D SMP Negeri 2 Panggul Trenggalek are found who are not able to make short stories frameworks, so the results are not satisfactory. This is evidenced by the 30 students of class VII consisting of 14 male students and 16 female students, 12 students who completed their studies or 40% of the students who did not complete their studies as many as 18 students or 60% with an average of 62 grades. 50. The value obtained by these students has not reached the specified KKM, which is 70. The purpose of this study is to obtain objective answers about improving Indonesian language learning achievement in short story writing materials through a Problem Based Learning Model with Serial Picture Media in class IX D students of SMP Negeri 2 Panggul Trenggalek. This research is a Classroom Action Research (CAR). The research was conducted in 2 cycles. Each cycle consists of four steps, namely planning, action, observation, and reflection. In the first cycle of learning, the test results are still low when compared to the results of the second cycle of tests. This is evidenced by the results of the first cycle test, the total score is 2220 with an average score of 74 and the percentage of completeness is 73%, while the second cycle test results total 2410 with an average value of 80.33 and a percentage of completeness 90%. Thus, it can be said that the results of the second cycle of research have increased from the results of the first cycle of research. The increase in the results of the research can be seen that the average of the first cycle is 74 for the second cycle of 80.33 so that there is an increase of 6.33. The completeness of the first cycle is 73%, the second cycle is 90% so that there is an increase of 17%. From the analysis of the data above, it can be concluded that through the Problem Based Learning (PBL) learning model, the achievement of learning Indonesian in short story writing material for students of SMP Negeri 2 Panggul Trengalek Class IX D of SMP Negeri 2 Panggul Trenggalek in Semester 1 of the 2019/2020 Academic Year has increased.